1990
DOI: 10.1177/001440299005700102
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Education Programs (IEPs) in Special Education—From Intent to Acquiescence

Abstract: Evaluations ofindividualized education programs (IE?s) over the past decade have pointed 10 an inoperative IE? process and a questionable document, A three-phased review oj" data-based research and position papersfrom 1975 to 1989 reveals a history 0(1 E? inadequacies and passive compliance. Thesefindings are in contrast to the original intent and spirit ofPublic Law 94-142, the Education/or All Handicapped Children. Act (EAHCA). Implications/or special education policy and practice have not been considered. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
6

Year Published

1992
1992
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 17 publications
4
80
0
6
Order By: Relevance
“…While there is substantial research regarding the potential effectiveness of IEP documents at the elementary school level (Avramidis & Silverstein, 2000;Capizzi, 2008;Dilberto & Brewer, 2012;Drasgow, Eric, Yell, Mitchell, Robinson, & Rowland, 2001;Fish, 2008;Garriot & Snyder, 2000;Huefner, 2000;Johns, Crowley, &, Guetzloe, 2002;Jung, Gomez, Baird & Keramidas, 2008;Lee-Tarver, 2006;Menlove, Hudson & Suter, 2001;Myers & Eisenman, 2005;Rose, Shevlin, Winter, O'Raw & Zhao, 2012;Sanches-Ferreira, Lopes-dos-Santos, Alves, Santos, & Silveira-Maia, 2013;Shriner & Destefano, 2003;Smith, 1990;Whitbread, Bruder, Fleming, & Park, 2007) IEP. There is a commitment from the administration to provide the necessary funds to ensure that teachers teaching on call (TTOCs) are present to release teachers so they can be present.…”
Section: Purposementioning
confidence: 99%
See 4 more Smart Citations
“…While there is substantial research regarding the potential effectiveness of IEP documents at the elementary school level (Avramidis & Silverstein, 2000;Capizzi, 2008;Dilberto & Brewer, 2012;Drasgow, Eric, Yell, Mitchell, Robinson, & Rowland, 2001;Fish, 2008;Garriot & Snyder, 2000;Huefner, 2000;Johns, Crowley, &, Guetzloe, 2002;Jung, Gomez, Baird & Keramidas, 2008;Lee-Tarver, 2006;Menlove, Hudson & Suter, 2001;Myers & Eisenman, 2005;Rose, Shevlin, Winter, O'Raw & Zhao, 2012;Sanches-Ferreira, Lopes-dos-Santos, Alves, Santos, & Silveira-Maia, 2013;Shriner & Destefano, 2003;Smith, 1990;Whitbread, Bruder, Fleming, & Park, 2007) IEP. There is a commitment from the administration to provide the necessary funds to ensure that teachers teaching on call (TTOCs) are present to release teachers so they can be present.…”
Section: Purposementioning
confidence: 99%
“…The resultant case studies demonstrated that one of the most challenging aspects of working with students to develop their IEPs is finding the time to meet. Drasgow et al (2001) highlighted Smith's (1990) view that the strain on a teacher's time can limit the development of a meaningful IEP. Further research by Johns et al (2002) discussed the fact that the time necessary to construct a meaningful IEP can be challenging to find.…”
Section: Myers and Eisenman (2005) Interviewed Six Teachers In Mid-atmentioning
confidence: 99%
See 3 more Smart Citations